Aphyosemion pamaense, a new killifish species (Cyprinodontiformes: Nothobranchiidae) from Cameroon - Agnese, Jean-Francois; Legros, Olivier; Cazaux, Benoite; Estivals, Guillain (Zootaxa, 2013)
Aphyosemion pamaense sp. nov. is described from the Pama River, a small tributary of the Nyong, in the surroundings of Pama, Cameroon. It belongs to the subgenus Chromaphyosemion Radda, 1971 and is distinguished from its relatives by a unique/diagnostic combination of characters: orange unpaired fins, an anal fin without spots, an orange throat and purple to blue-grey flanks. The new species is also genetically differentiated from all the other Chromaphyosemion species as revealed by mtDNA (cytochrome b) analysis and characterised by a unique karyotype showing tentative sex chromosomes with 2n=35 chromosomes in males versus 2n=36 in females.